2020
DOI: 10.1111/ejn.15002
|View full text |Cite
|
Sign up to set email alerts
|

Can genetic polymorphisms predict response variability to anodal transcranial direct current stimulation of the primary motor cortex?

Abstract: Genetic mediation of cortical plasticity and the role genetic variants play in previously observed response variability to transcranial direct current stimulation (tDCS) have become important issues in the tDCS literature in recent years. This study investigated whether inter‐individual variability to tDCS was in‐part genetically mediated. In 61 healthy males, anodal‐tDCS (a‐tDCS) and sham‐tDCS were administered to the primary motor cortex at 1 mA for 10‐min via 6 × 4 cm active and 7 × 5 cm return electrodes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 148 publications
(368 reference statements)
0
11
1
Order By: Relevance
“…This recent work does not include any genotyping, but it does provide the simulation of the applied tDCS montage and the resulting differences in cortical excitability. While no significant effect of the anodal tDCS on the MEP amplitude was found in Pellegrini et al (2021c), a very significant effect was found in the present study (Pellegrini et al, 2021a). The authors do not comment on this discrepancy.…”
Section: Introductioncontrasting
confidence: 81%
See 3 more Smart Citations
“…This recent work does not include any genotyping, but it does provide the simulation of the applied tDCS montage and the resulting differences in cortical excitability. While no significant effect of the anodal tDCS on the MEP amplitude was found in Pellegrini et al (2021c), a very significant effect was found in the present study (Pellegrini et al, 2021a). The authors do not comment on this discrepancy.…”
Section: Introductioncontrasting
confidence: 81%
“…And their answer is “Yes” if we find a way to personalize it. A very effective way to do that would be through usage of biomarkers (like gene polymorphisms) and this is where the paper by Pellegrini et al (2021a) attempts to give its contribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, we know that tES can alter GABA concentration, even in unstimulated brain regions [70,71], and that this directly relates to performance in a behavioural task [72][73][74]. We also know that neurochemical 'state' determines the capacity to undergo tES-induced cortical plasticity [45,75,76]. For example, the relative concentrations of both GABA and glutamate in prefrontal cortex determine the impact of tES on performance in a response to a selection task [77].…”
Section: How Generalisable Are Cfms?mentioning
confidence: 99%